The Mollycoddle Based on a Short Story by Harold McGrath - Carli, Philip; McGrath, Harold (Douglas Fairbanks: A Modern Musketeer, 2008)
After finishing his first costumer swashbuckler "The Mark of Zorro", Douglas Fairbanks Sr. reverted to his standard formula with the contemporary action comedy "The Mollycoddle". Doug plays the title character, a dandified American who returns to his home in the Wild West after being educated in England. Suspected of being little more than a pantywaist, Doug proves his grit by capturing notorious desperado Wallace Beery. Fairbanks and Tom Geraghty co-adapted "The Mollycoddle" from a short story by Harold McGrath. He followed this picture with another modern comedy, "The Nut", then devoted the rest of the 1920s to such period pictures as "Robin Hood", "The Thief of Baghdad" and "The Gaucho". [www.rottentomatoes.com]